Kinerja Berthing Time terhadap Bongkar Muat Gandum Curah Kering di Kapal Mv. Green Sapphire pada PT. Gelora Perkasa Belawan - Juaro Sonang Tampubolon; Suratni Ginting; Lilis Lilis (KALAO'S MARITIME JOURNAL, 2025)
This study aims to analyze the effect of berthing time performance on the loading and unloading process of dry bulk wheat on the MV Green Sapphire ship at PT. Gelora Perkasa Belawan. The research methods used in writing this paper are field research and library research methods. Berthing time performance has a significant influence on the smoothness and efficiency of the loading and unloading process of dry bulk wheat on the MV. Green Sapphire ship at PT. Gelora Perkasa Belawan. Optimal berthing time can accelerate the completion of loading and unloading activities, minimize operational costs, and increase company productivity. Supporting factors such as equipment readiness, workforce skills, and coordination with port authorities play an important role in achieving work targets. Conversely, obstacles such as bad weather, equipment damage, and dock congestion can extend berthing time and reduce efficiency. Therefore, planned operational management, routine equipment maintenance, administrative digitalization, and good coordination between related parties are needed to ensure berthing time remains effective and the loading and unloading process takes place safely, quickly, and efficiently.